2016
DOI: 10.1515/jas-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Phenology of Selected Linden (TiliaL.) Taxa in Relation to Pollen Seasons

Abstract: A b s t r a c t All lindens provide Apidae insects with nectar, pollen, and honeydew. Lindens are important melliferous trees in Poland. The first purpose of the study was to carry out phenological observations of the flowering in ten linden taxa. The second aim was to analyse the content of linden pollen grains in the air of Lublin. A correlation between the parameters of the pollen season and meteorological factors was also determined. This study was conducted in the city of Lublin located in the central-eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The five studied oilseed rape cultivars showed similar trends, with higher pollen counts in the full bloom stage than in the initial and late flowering stages. It has been proved that the highest pollen number of linden trees is the full flowering stage, which was consistent with the results in this paper (Weryszko-Chmielewska et al, 2010). The high pollen count in the full bloom stage implied that there may be higher reproductive pressure in this stage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The five studied oilseed rape cultivars showed similar trends, with higher pollen counts in the full bloom stage than in the initial and late flowering stages. It has been proved that the highest pollen number of linden trees is the full flowering stage, which was consistent with the results in this paper (Weryszko-Chmielewska et al, 2010). The high pollen count in the full bloom stage implied that there may be higher reproductive pressure in this stage.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the pollen count of a single flower in cabbage cultivars has been found to range from 20,000 to 858,000 grains (Sun et al, 2020). It has also been demonstrated that the pollen counts of linden trees vary dynamically among different flower stages, with the highest pollen count occurring at the anthesis stage (Weryszko-Chmielewska et al, 2010). In addition, the number of pollen Brassicaceae grains also changed (Masierowska, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Lublin, it has been shown that among four species of Acer (maple tree), A. negundo and A. platanoides are responsible for the majority of Acer pollen in the air (Weryszko-Chmielewska et al, 2016). In contrast, among 10 lime tree species, Tilia cordata was the most important pollen contributor (Dąbrowska et al, 2016). e pollen production and flowering phenology of three Artemisia species have been compared to airborne pollen season in Poznań (Bogawski et al, 2016).…”
Section: Relationship Between Phenology and Bioaerosols Concentrationmentioning
confidence: 99%